(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The images that are the critical and important images which contain visual, useful and meaningful information that cannot be observed by an ordinary person are medical images. Medical images are usually saved for the future purpose. The retrieve process is the method that brings the similar images from a database. The main objective of Image retrieving techniques is to bring out the maximum nearest image to the input query image based on some standard features. In this paper, it is analysed the state of art image retrieving models in the area of medical image processing